IMAN KATOLIK MEMANDANG BERBAGAI PRAKTIK TERAPI ALTERNATIF - Christanto, Cahyo (Jurnal Teologi (Journal of Theology), 2013)
There are various efforts to achieve a cure: the effort through prayer, through the efforts of conventional medicine and the effort through alternative therapies. The fact that sometimes happens is that the methods that work in synergy but often walk alone or even contradictory. For Catholics, this can make the faithful confused and wondering. It can also cause the pros and cons of them. This study aims to formulate the principles of assessment of alternative therapies, in the light of the Catholic faith, as well as offering pastoral steps on alternative therapies. For that, researcher first learns the concepts of healing in Scripture, learns and explores the ins and outs of alternative therapies in detail in the traditions and culture of the East, conducts a review of some alternative therapies with the help of theoretical Physics of Electricity, Epigenetics, Quantum Physics, and Brain Wave theory. To that end, researcher uses the means of interviews with some practitioners of alternative therapies and conducts the study of supportive literature. After reflecting theologically the concept and practice of alternative therapies in the light of the Catholic faith, this research proposes the principles of assessment of the Church on alternative therapies and pastoral steps. With the wise principle of assessment, the Church can help the faithful to, with a clear conscience, take a critical attitude toward alternative therapies.